Multiculturalism and Territorialization: An example in the Transitional Society - Čaldarović, Ognjen (2004)
Multiculturalism and territoriality are interconected. Changes after 1980s in post-socialistic societies (and Croatia) show social differentiation and social segregation as consuquences of "ethnic territorialization" and new situation and characteristic as well.
Nedostaje podatak o stranicama. (admin.)
Projekt MZOS
ENG